2021
DOI: 10.2147/ndt.s299462
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-to-Lymphocyte Ratio is Associated with Depression 3 Months After Stroke

Abstract: To explore the relationship between the monocyte-to-lymphocyte ratio (MLR) and depression three months after acute ischemic stroke. Patients and Methods: From May 2013 to September 2014, 203 patients with acute ischemic stroke were recruited within 7 days post-stroke from Shanghai Ruijin Hospital and blood samples were collected after admission. The Hamilton Depression Scale and Clinical Review were evaluated at 3 months after stroke. Based on the Diagnostic and Statistical Manual of Mental Disorders-IV diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…proposed that higher neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio were correlated with PSD at 6 months ( 49 ), and Ding et al. found that monocyte-to-lymphocyte ratio was in association with depression 3 months after stroke ( 50 ). But these associations were not shown in current study.…”
Section: Discussionmentioning
confidence: 99%
“…proposed that higher neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio were correlated with PSD at 6 months ( 49 ), and Ding et al. found that monocyte-to-lymphocyte ratio was in association with depression 3 months after stroke ( 50 ). But these associations were not shown in current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the inflammatory mediators used in the present research could be derived from the findings of a full blood count examination, they are simple to use and affordable to obtain. It has been shown that the MLR may function as a biomarker for both systematic inflammatory responses and neuroinflammation in individuals suffering from depression 34 . It is common practice to utilize inflammatory markers found in regular blood testing to predict the prognosis of POD, and these indicators represent the extent of systemically low‐intensity inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, more recent evidence highlighted the effect of inflammation on the mood of COPD (Ding et al, 2021;Long et al, 2020). Systemic inflammation runs through the COPD patient's entire life cycle because of the disease, from the airways to the target organs and tissues throughout the body and may be related to its comorbidities such as anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%